Correlation between diffusion barriers and alloying energy in binary alloys. Issue 4 (11th January 2016) - Vej-Hansen, Ulrik Grønbjerg; Rossmeisl, Jan; Stephens, Ifan E. L.; Schiøtz, Jakob
Abstract : In this paper, we explore the notion that a negative alloying energy may act as a descriptor for long term stability of Pt-alloys as cathode catalysts in low temperature fuel cells. Abstract : In this paper, we explore the notion that a negative alloying energy may act as a descriptor for long term stability of Pt-alloys as cathode catalysts in low temperature fuel cells. Using density functional theory calculations, we show that there is a correlation between the alloying energy of an alloy, and the diffusion barriers of the minority component. Alloys with a negative alloying energy may show improved long term stability, despite the fact that there is typically a greater thermodynamic driving force towards dissolution of the solute metal over alloying. In addition to Pt, we find that this trend also appears to hold for alloys based on Al and Pd.